2023
DOI: 10.3390/v15112216
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplexes in the Viral Genome: Unlocking Targets for Therapeutic Interventions and Antiviral Strategies

Rajiv Pathak

Abstract: G-quadruplexes (G4s) are unique non-canonical four-stranded nucleic acid secondary structures formed by guanine-rich DNA or RNA sequences. Sequences with the potential to form quadruplex motifs (pG4s) are prevalent throughout the genomes of all organisms, spanning from prokaryotes to eukaryotes, and are enriched within regions of biological significance. In the past few years, the identification of pG4s within most of the Baltimore group viruses has attracted increasing attention due to their occurrence in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…An example of the functional relevance of G-quadruplexes in viral genomes was provided in a reporter assay of PQS-containing human cytomegalovirus (HCMV) regulatory sequences, where chemically induced G-quadruplex stabilization resulted in transcriptional suppression of some of the tested viral promoters [ 200 ], suggesting that these secondary structures can be used as targets for specific antiviral drugs (reviewed in ref. [ 201 , 202 ]). Interestingly, a fraction of the predicted G4-forming sequences from the unicellular eukaryote Saccharomyces cerevisiae was found to be conserved in other fungal species [ 203 ], with these sequences being enriched in promoters, telomeres, rDNA, mtDNA, and sites of frequent double-strand breaks [ 203 , 204 ].…”
Section: Prevalence Of Guanine Tetraplexes In Genomesmentioning
confidence: 99%
“…An example of the functional relevance of G-quadruplexes in viral genomes was provided in a reporter assay of PQS-containing human cytomegalovirus (HCMV) regulatory sequences, where chemically induced G-quadruplex stabilization resulted in transcriptional suppression of some of the tested viral promoters [ 200 ], suggesting that these secondary structures can be used as targets for specific antiviral drugs (reviewed in ref. [ 201 , 202 ]). Interestingly, a fraction of the predicted G4-forming sequences from the unicellular eukaryote Saccharomyces cerevisiae was found to be conserved in other fungal species [ 203 ], with these sequences being enriched in promoters, telomeres, rDNA, mtDNA, and sites of frequent double-strand breaks [ 203 , 204 ].…”
Section: Prevalence Of Guanine Tetraplexes In Genomesmentioning
confidence: 99%
“…13 In recent years, there have been several studies focused on identifying G4s in the HBV genome and to elucidate their role in the viral life cycle. 14,15 Through a comprehensive biophysical and cell biology approach, our previous research has shown the existence of a highly ordered parallel G-quadruplex (G4) structure in the EnhII/PreC promoter region of the HBV genome and its role in regulating HBV core protein translation. 16 Moreover, researchers have also identified 12 potential quadruplex-forming sequences (PQS), some of which have been attributed to have roles in cccDNA phase separation, as well as regulation of HBsAg and HBcAg production.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been several studies focused on identifying G4s in the HBV genome and to elucidate their role in the viral life cycle 14,15 . Through a comprehensive biophysical and cell biology approach, our previous research has shown the existence of a highly ordered parallel G‐quadruplex (G4) structure in the EnhII/PreC promoter region of the HBV genome and its role in regulating HBV core protein translation 16 .…”
Section: Introductionmentioning
confidence: 99%